The plasticating sequence In barrier extrusion screws part II: Experimental assessment - Gaspar-Cunha, A. (2014)
A modular laboratorial single screw extruder was used to perform screw pulling experiments and generate data on the development of plasticating of two polymers along the axis of a Maillefer barrier screw. The effects of the presence of the barrier (by comparison with an equivalent conventional 3-zone screw), of its geometrical parameters and of operating conditions were investigated and compared to the predictions provided by a previously developed computational model. Although the small size of the extruder influenced solids conveying and induced premature and quick melting, the two sets of data were generally in satisfactory agreement.